From a simple EHR to the market lead: learnings from Portugal and Spain - Silva, Maria Madalena Cabrita Menezes da (2022)
An Electronic Health Record (EHR) stores the patients’ medical history over time, leverages the quality of service, and reduces medical errors. However, despite the potential of thesoftware,theexistingliteraturepointstoreducedusersatisfactionandtoseveralissuesassociatedwiththeEHRfunctioning.Therefore,thisprojectconcludesontheusers’satisfaction in Portugal and Spain, identifies the difficulties they face and their impact, and theconsumerneedsthatarenotbeingfulfilled.TheresultssuggestthatEHRvendorsshouldinvestin user-friendly software, leverage access to information, streamline workflow, and promote training to offer a market-leading product.